Place and time in the Criminology of Place - Bannister, Jon (Theoretical criminology, 2019)
This article evaluates developments in the ecological analysis of crime, which have found their most recent expression in a Criminology of Place. We argue that theoretical and methodological deficiencies are evident in the Criminology of Place and associated literatures with respect to their underlying treatment of place, time and causation. Big Data holds promise for helping address these shortfalls, but dangers also. The successful advance of the Criminology of Place requires elevating the why question to equal status with those of where and what in the analysis of crime. Ultimately, the paper positions the progress towards and prospects for a multi-scalar and time sensitive theoretical and empirical model of the Criminology of Place.